Chapter 1 Introduction - Mellemvik, Frode (Taylor & Francis, 2015)
Will Arctic states cooperate in the development of Arctic petroleum resources? This is what they declare, but the barriers to the cooperative development of Arctic petroleum resources are intensifying and the future is unclear.